2019
DOI: 10.3389/fpls.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Global Responses of Resistant and Susceptible Sorghum (Sorghum bicolor) to Sugarcane Aphid (Melanaphis sacchari)

Abstract: The sugarcane aphid ( Melanaphis sacchari ) has emerged as a significant pest for sorghum. The use of sugarcane aphid-resistant sorghum germplasm with integrated pest management strategies appears to be an excellent solution to this problem. In this study, a resistant line (RTx2783) and a susceptible line (A/BCK60) were used to characterize the differences in plant responses to the sugarcane aphid through a series of experiments, which examined global sorghum gene expression, aphid feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 76 publications
5
33
0
Order By: Relevance
“…The EPG results imply that the aphids settled and started probing more swiftly on the leaf of RTC-144 and spend less time non-probing than RTC-406. A recent study assessed the potential surface resistance of sorghum plants to sugarcane aphids ( Melanaphis sacchari ) and suggested that the aphids spend approximately twice longer in the non-probing phase in the resistant plants than in the susceptible plants ( Tetreault et al, 2019 ). Barley leaves infested with R. padi showed a shorter time of salivation and ingestion of the phloem on resistant relative to the susceptible plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The EPG results imply that the aphids settled and started probing more swiftly on the leaf of RTC-144 and spend less time non-probing than RTC-406. A recent study assessed the potential surface resistance of sorghum plants to sugarcane aphids ( Melanaphis sacchari ) and suggested that the aphids spend approximately twice longer in the non-probing phase in the resistant plants than in the susceptible plants ( Tetreault et al, 2019 ). Barley leaves infested with R. padi showed a shorter time of salivation and ingestion of the phloem on resistant relative to the susceptible plants.…”
Section: Discussionmentioning
confidence: 99%
“…Barley leaves infested with R. padi showed a shorter time of salivation and ingestion of the phloem on resistant relative to the susceptible plants. Feeding patterns reflect many factors, including mechanical barriers present at the leaf surface, olfactory repellents, and host metabolism ( Tetreault et al, 2019 ). The results highlight the need for conducting multiple bioassays combined with metabolic and transcriptomic methods to expose the mode of defense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, sugarcane aphid (SCA) emerged as a major insect pest of sorghum crops in North America (Alkan et al 2011). The line Tx2783 is highly resistant to SCA, and thus has great potential to boost breeding targeted at aphid resistance (Tetreault et al, 2019) ( Fig. 7B).…”
Section: Nbs-lrr Genes In Sorghum Genomesmentioning
confidence: 99%
“…To investigate how gene expression is impacted by SCA, we remapped the RNA-Seq data before and after sugarcane aphid infestation from a previous study (Tetreault et al, 2019) to our Tx2783 genome. Gene expression analysis revealed that five out of the ten R genes expressed before and after SCA infestation ( Fig.…”
Section: Nbs-lrr Genes In Sorghum Genomesmentioning
confidence: 99%